2020
DOI: 10.1002/eat.23348
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth transition in a comprehensive care unit for eating disorders: Challenges and long‐term benefits

Abstract: The 2019 novel coronavirus disease (COVID-19) pandemic has forced many eating disorder medical stabilization units to consider adjustments that uphold both the quality of care delivered to patients while also observing social distancing public health directives for patients and staff. To date, inpatient facilities for eating disorders (both medical stabilization units and higher level of care facilities) have not needed to consider how to translate services to electronic platforms, given that most of these pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 15 publications
2
52
1
2
Order By: Relevance
“…With regard to patient perceptions of tele-therapy, the majority of participants cited having a positive experience that was akin to, if not preferred to, in-person therapy. These findings are also inconsistent with the limited literature that exists on this topic, in which patients were found to generally prefer in-person therapy to tele-therapy (Datta et al, 2020;Fernández-Aranda et al, 2020), although in Datta et al (2020), these preferences were cited in the context of an inpatient sample. In our study, tele-therapy was viewed positively in large part due to the convenience and accessibility of this modality of therapy.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…With regard to patient perceptions of tele-therapy, the majority of participants cited having a positive experience that was akin to, if not preferred to, in-person therapy. These findings are also inconsistent with the limited literature that exists on this topic, in which patients were found to generally prefer in-person therapy to tele-therapy (Datta et al, 2020;Fernández-Aranda et al, 2020), although in Datta et al (2020), these preferences were cited in the context of an inpatient sample. In our study, tele-therapy was viewed positively in large part due to the convenience and accessibility of this modality of therapy.…”
Section: Discussioncontrasting
confidence: 83%
“…Qualitative findings from pilot study found that patients missed the structure of in-person treatment and weekly weigh-ins (Fernández-Aranda et al, 2020). In another qualitative exploration of patient perceptions of group therapy, while the majority failed to cite dislikes of virtual groups, the general consensus was a preference for connectedness of in-person groups (Datta, Derenne, Sanders, & Lock, 2020). The research thus far regarding eating disorder patient perceptions of tele-therapy has been limited to quantitative analysis of the frequency of tele-therapy use or informal assessments of patient perceptions of group therapy.…”
mentioning
confidence: 99%
“…While some evidence exists (see for example Wade et al 2020;Dross et al 2020;Datta et al 2020), we do not yet clearly know which people facing which presenting problems will be best suited to maintaining this way of working. Likewise, it is not yet clear how families find remote service delivery.…”
Section: Limitations Of the Project And Future Directionsmentioning
confidence: 91%
“…Additionally, acceptance of telemedicine may vary by ED subtype, with evidence suggesting that individuals with the anorexia nervosa subtype may be least content with the transition to remote treatment [12]. In inpatient settings, care teams have been reduced in size, visitations have been limited, and admission criteria have become more stringent [16,17,20]. To abide by social distancing guidelines, group therapy sessions have been cancelled or conducted remotely, limiting patients' access to familiar social support networks, though also reducing opportunity for body comparisons [20].…”
Section: Introductionmentioning
confidence: 99%
“…In inpatient settings, care teams have been reduced in size, visitations have been limited, and admission criteria have become more stringent [16,17,20]. To abide by social distancing guidelines, group therapy sessions have been cancelled or conducted remotely, limiting patients' access to familiar social support networks, though also reducing opportunity for body comparisons [20]. Additionally, physical and financial barriers to treatment may arise among patients with limited computer or internet access [18] and among those whose income has been adversely affected by business closures.…”
Section: Introductionmentioning
confidence: 99%